2015
DOI: 10.1002/mus.24561
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the log‐transformed EMG amplitude‐power output relationship for incremental knee‐extensor ergometry

Abstract: The log-transformed EMG amplitude-power output relationship is a reliable index for measuring motor unit activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(54 citation statements)
references
References 29 publications
0
54
0
Order By: Relevance
“…The investigator concluded that the rectus femoris during walking was active during the stance-to-swing transition, but that as the pace increased, the EMG activity increased during the swing-to-stance transition (29). The exercise mode used in current study is the single-leg knee-extensor ergometry, which isolates the quadriceps femoris muscles while concomitantly minimizing cardiovascular and respiratory responses to exercise (9,13,24,25,32). Moreover, Richardson et al (32) reported that the rectus femoris muscle had the highest activation compared with the vastus lateralis, vastus medialis, and vastus intermedius muscles for single-leg knee-extensor ergometry.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The investigator concluded that the rectus femoris during walking was active during the stance-to-swing transition, but that as the pace increased, the EMG activity increased during the swing-to-stance transition (29). The exercise mode used in current study is the single-leg knee-extensor ergometry, which isolates the quadriceps femoris muscles while concomitantly minimizing cardiovascular and respiratory responses to exercise (9,13,24,25,32). Moreover, Richardson et al (32) reported that the rectus femoris muscle had the highest activation compared with the vastus lateralis, vastus medialis, and vastus intermedius muscles for single-leg knee-extensor ergometry.…”
Section: Discussionmentioning
confidence: 98%
“…Incremental Single-Leg Knee-Extensor. The single-leg kneeextensor ergometry has been used previously in our laboratory (9,13,24,25,32) and exclusively focuses the exercise demand on the quadriceps femoris muscles (32). Briefly, each participant was semirecumbent in an adjustable chair with a special ankle boot placed on the nondominant leg and connected by a bar to the ergometer.…”
Section: Methodsmentioning
confidence: 99%
“…In muscle work, during the swing period, activation and contraction of the gastrocnemius muscle causes the calf to flex at the knee joint, which is crucial for movement completion (Prateepavanich et al ., 1999). There is a good linear relationship between the muscle contractility or output power changes and EMG signal amplitude under various muscle‐loading forms (Eason et al ., 2015). ID children's left‐leg gastrocnemius EMG value was significantly lower than TD children, indicating non‐development of a complete gait pattern and a lack of ground thrusting and also unbalanced development of the lower limb gastrocnemius muscle, resulting in a lack of coordination on both sides (Donath et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…where the exponent Y is equal to the predicted EMG amplitude, X is the power output, and b is the slope of the logtransformed equation (5,12,25,34). Therefore, using equation 2, values such as the coefficient of determination (R 2 ), slope, and yintercept were calculated on a subject-by-subject basis.…”
Section: Statistical Analysesmentioning
confidence: 99%